2010
DOI: 10.1007/s11104-010-0572-2
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of persistent effects of continuously planted transgenic insect-resistant cotton on soil microorganisms

Abstract: Transgenic insect-resistant cotton expressing the Cry1Ac and/or CpTI protein has been released into the environment for commercial cultivation for over a decade in China. In this consecutive 3-year field study (2007)(2008)(2009), we characterized the microbial populations in two different transgenic cotton fields and one non-transgenic cotton field to assess the environmental impact of long-term cultivation of transgenic insect-resistant plants in credible field conditions. We obtained samples at four differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 43 publications
(45 reference statements)
6
32
1
Order By: Relevance
“…However, no overall consistent trends in physicochemical properties were detected in the two soil environments, over the three-year study, or in the four growth stages. This result is consistent with previous results in other plants and fields [32]. …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…However, no overall consistent trends in physicochemical properties were detected in the two soil environments, over the three-year study, or in the four growth stages. This result is consistent with previous results in other plants and fields [32]. …”
Section: Resultssupporting
confidence: 94%
“…However, no consistent trends in enzyme activity were detected in the two soil environments, over the three-year study, or in the four growth stages analyzed here. These results agree with those of previous studies in other regions and for a variety of crops [2932]. …”
Section: Resultssupporting
confidence: 93%
“…The long-term cultivation of transgenic plants may or may not affect the diversity of soil microbial community (Li et al, 2011). The cultivation of transgenic maize and cotton has not shown any significant effect on rhizospheric properties as compared to wild type counterpart (Flores et al, 2005;Griffiths et al, 2006;Shen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Priestley and Brownbridge 30 studied the impact of some Bt transgenic silage corn lines on non-target soil arthropods and reported that transgenic plants had no negative effect on any of the organisms analyzed, but there was a significant year effect on the abundance and diversity of some taxa. Li et al 31 studied the effect of Bt cotton continuously planted for many years on soil microorganisms in a three-year field experiment. These authors also reported that no significant difference in the abundance or diversity indexes could be attributable to long-term cultivation of transgenic cotton, but there was significant seasonal variation in the number of soil microorganisms collected in Bt cotton plots.…”
Section: Discussionmentioning
confidence: 99%